FAKTOR-FAKTOR PENDUKUNG KEBERLANJUTAN USAHATANI KOPI ARABIKA DI PROVINSI BALI - Dewi, Ida Ayu Listia; Sudarma, I Made (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Coffee is the mainstay of Balinese exports. But the productivity of Balinese Arabica coffee is still low. The sustainability of Bali Arabica Coffee farming is threatened. The purpose of this study was to determine the factors driving the sustainability of Arabica coffee farming in Bali. The research location is the Arabica coffee production center in Bali Province. The method of determining the number of sampling based on the Slovin formula with an error rate of 15% is 52 farmers. The method of determining sampling is based on random sampling. The economic dimension shows that Arabica coffee farm income in Bali in 2019 per average area of ??arable land by farmers (0.86 ha) is Rp 22,820,376. Contribution of income from Arabica coffee farming in Bali to family income is 69.07%. Farming Experience (X22), farmer age (X20), and farmer education (X21) are components of Social Factors. Making rorak (X13), number of family members (X23), replanting (X12), use of quality local seeds (X11), farmers know the condition of their land (X10) representing environmental factors. The use of shade (X14), plant age (X5), use of clean water (X9), and harvesting of red picks (X19) are the components forming the Technology Factor.